Hubungan Durasi Penggunaan Smartphone dengan Kejadian Tension-Type Headache pada Mahasiswa Keperawatan - Sarah Alatas; Muhammad Isman Jusuf; Sri Yulian Hunowu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the relationship between smartphone usage duration and tension-type headache incidence in nursing students at Gorontalo State University. The method used was quantitative with an observational analytical design and a cross-sectional approach. The results showed a p-value of 0.001 (<0.05), indicating a significant relationship between smartphone usage duration and tension-type headache incidence in nursing students at Gorontalo State University. In conclusion, the longer the smartphone usage duration, the higher the likelihood of experiencing tension-type headache. Keywords: Smartphone Usage Duration, Tension-Type Headache